SGXGauge: A Comprehensive Benchmark Suite for Intel SGX - Kumar, Sandeep; Panda, Abhisek; Sarangi, Smruti R. (2022 IEEE International Symposium on Performance Analysis of Systems and Software (ISPASS), 2022)
Trusted execution environments (TEEs) such as Intel SGX facilitate the secure execution of an application on untrusted machines. A plethora of work focuses on improving the performance of such environments necessitating the need for a standard, widely accepted benchmark suite. We present SGXGauge, a benchmark suite for SGX containing a diverse set of workloads from different domains. We also thoroughly characterize the behavior of the benchmark suite on a native platform and on a platform that uses a library OS-based shim layer (GrapheneSGX).